2018
DOI: 10.1016/j.jcot.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The top 10 arthroplasty articles published in last 10 years by Indian authors

Abstract: Joint replacement surgery is becoming increasingly popular globally and recently,​in India. The phenomenon of medical tourism has also contributed to increasing number of arthroplasty surgeries being done every year in our country. The surgeons who work in this highly specialized field of orthopedic surgery, have been publishing their research work in reputed journals. In this paper, we have discussed the most cited Indian papers in the field of arthroplasty. It was observed that publications in high impact an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 60 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…The Indian Arthroplasty surgeons have now also started been publishing their research work in reputed journals. In a systematic review, Vaishya et al 17 of the most cited Indian papers in the last ten years and observed that publications in high impact and reputed journals attracted more citations and created more impact. It was therefore recommended that the researchers should submit their 'good' scientific research work to such journals.…”
mentioning
confidence: 99%
“…The Indian Arthroplasty surgeons have now also started been publishing their research work in reputed journals. In a systematic review, Vaishya et al 17 of the most cited Indian papers in the last ten years and observed that publications in high impact and reputed journals attracted more citations and created more impact. It was therefore recommended that the researchers should submit their 'good' scientific research work to such journals.…”
mentioning
confidence: 99%